2019
DOI: 10.1111/arcm.12500
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of some plant extracts and essential oils against fungi‐infested organic archaeological artefacts

Abstract: The determination of the antifungal activities of nine kinds of powdered plant extracts and five essential oils was studied in vitro against four of the most common fungal species (Aspergillus flavus, A. versicolor, Penicillium sp. and P. purpurogenum), which were isolated from different organic materials from archaeological artefacts such as papyrus and linen. The essential oils showed greater efficacy than the powdered plant extracts, where thyme and lemongrass oils were the most potent. Also, the minimum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…They were divided into three groups depending on the magnification ×1000, ×300 and ×100 LM. In the analysis of the SEM images of textiles, the most commonly used way of their digital representation is textural features [37,38]; the advantage of using textural features in the analysis of SEM images is that they can be used to analyze, model and process the texture. In this way, human vision is simulated by distinguishing elements in images.…”
Section: Resultsmentioning
confidence: 99%
“…They were divided into three groups depending on the magnification ×1000, ×300 and ×100 LM. In the analysis of the SEM images of textiles, the most commonly used way of their digital representation is textural features [37,38]; the advantage of using textural features in the analysis of SEM images is that they can be used to analyze, model and process the texture. In this way, human vision is simulated by distinguishing elements in images.…”
Section: Resultsmentioning
confidence: 99%
“…Essential oil (EO) is a natural alternative because it has the ability to protect archaeological objects [ 1 , 2 , 3 , 4 , 5 , 6 ]. It can be used to inhibit microbial growth because of its biodegradability, cost-effectiveness, environmental suitability, non-toxicity, antimicrobial, and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although a limited number of studies have focused on demonstrating the efficiency of R. officinalis extract against biodeteriogenic microorganisms, the antifungal activity of R. officinalis extracts (water and ethanol) against four fungal strains ( A. flavus , A. versicolor , Penicillium spp., P. purpurogenum ) isolated from different archaeological artefacts in an Egyptian Museum demonstrated the efficiency of both extracts [ 52 ]. Several other authors have demonstrated the antimicrobial activity of R. officinalis EO or of the crude extract against several food-borne pathogens, for i.e., against Macrophphaseolina phaseolina to control charcoal rot in Glycine max [ 53 ].…”
Section: Discussionmentioning
confidence: 99%